Reliability Analysis of Autoflight Servo System Failures: A Case Study of the Airbus A330-300 at International Airline X - Akhmad Satriyo; Mufti Arifin; M. Hadi Widanto (FTK UNSURYA, 2026)
The autoflight servo system plays a critical role in maintaining aircraft stability during automated flight operations, where sustained manual control by the pilot is impractical. Due to its integration with multiple aircraft systems, servo failures may propagate and affect overall flight control performance. This study investigates the failure characteristics, root causes, and mitigation strategies of the autoflight servo system in the Airbus A330-300 operated by International Airline X. A descriptive quantitative approach was adopted using a case study methodology. Primary data were obtained from maintenance records, technical documentation, and interviews with relevant personnel, while secondary data included historical failure reports and repair procedures. Risk Priority Number and fishbone diagram was employed to identify dominant failure mechanisms. The results indicate that failures were primarily electrical (27.91%), followed by mechanical (20.93%), hydraulic (17.44%), and human error (6.98%). Electrical failures represent the highest risk category. In response to servo failure, the system automatically transitions to Secondary Flight Control Computer (SEC) or alternate law mode, allowing pilot control via sidestick input. Preventive measures include periodic connector cleaning (1–2 years) and actuator seal monitoring through hydraulic oil particle analysis to detect early wear.